2022
DOI: 10.3389/fvets.2022.1004637
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of cranial cruciate ligament disease in dogs using Tibial Plateau Leveling Osteotomy or Tibial Tuberosity Advancement–A systematic review with a meta-analytic approach

Abstract: Tibial Plateau Leveling Osteotomy (TPLO) or Tibial Tuberosity Advancement (TTA) are commonly used surgical techniques for correction of cranial cruciate ligament (CCL) rupture in dogs. This systematic review aims to investigate whether one technique is superior to the other. Seventy-two studies on surgical management of CCL rupture have been identified and evaluated in regard of subjective and objective gait analysis criteria, development of osteoarthritis (OA), thigh circumference measurements, goniometry, jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…Increasing bodyweight has been reported as a risk factor for complications after CCLD surgery, for OA development and for CCLD-related euthanasia, but the effect of bodyweight on the outcome in dogs with CCLD is not commonly evaluated in the literature. 17,[49][50][51][52][53][54][55] Based on the results of the current study, bodyweight could possibly affect long-term stiffness and lameness in dogs with CCLD, with an increased risk in heavier dogs. Future prospective randomised clinical trials that evaluate the effect of treatment and bodyweight on the long-term outcome in dogs with CCLD are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing bodyweight has been reported as a risk factor for complications after CCLD surgery, for OA development and for CCLD-related euthanasia, but the effect of bodyweight on the outcome in dogs with CCLD is not commonly evaluated in the literature. 17,[49][50][51][52][53][54][55] Based on the results of the current study, bodyweight could possibly affect long-term stiffness and lameness in dogs with CCLD, with an increased risk in heavier dogs. Future prospective randomised clinical trials that evaluate the effect of treatment and bodyweight on the long-term outcome in dogs with CCLD are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] The outcome after surgical treatment of CCLD is generally reported as successful, [10][11][12][13][14][15][16] although highquality studies comparing the intermediate-to longterm outcome in dogs treated with different surgical techniques are sparse. 8,17 According to a recent review of TPLO and TTA, there is not enough evidence to support one method over the other. 17 However, a couple of earlier reviews concluded that TPLO is the method most likely to return dogs to normal function 8 and is associated with lower complication rates, improved clinical-functional outcomes and less osteoarthritis (OA) progression than TTA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations